Vloga endocitotskih poti pri razvoju in zdravljenju bolezni - Lojk, Jasna (Medicinski razgledi, 2013)
A cell is separated from its environment by the plasrna membrane through which it accepts signals and nutrients. The plasrna membrane also allows celi ul ar response to them. Endocytosis has a key role in these processes. It provides and regulates many cellular processes, including celi signalling, celi polarity establishment, celi growth and differentiation. Manyentry patlrways into cells have been identified, which differ in terms of different types of cargo internalized and specific molecules that allow the endocytic process. The endocytic pathway starts with the selection of cargo at the celi surface, and is followed by invagination of plasrna membrane and formation of endocytic vesicles. These vesicles, through interactions with other cellular compartments, deliver its cargo and membrane proteins to different locations in the celi or recycle them back to the plasrna membrane and the extracellular matrix. Endocytic pathways can be us ed for drug delivery for therapeutic purposes, but unfortunately they are also exploited by pathogens to enter the cells. Changes in endocytic pathways may be the reason for many diseases and their understanding is therefore important for effective treatment of these diseases. In this review article, we have gathered known facts about different types of endocytosis and endocytic pathways. We also discuss their role in the development of diseases and treatments.
Keywords: endocitoza; endocytosis; entry of pathogens; vstop patogenov; endosome; endosomi; lizosomi; lysosome; nanodelci; nanoparticles; vesicle maturation; zorenje veziklov